Early Molecular Detection of Invasive Alien Plants in Urban and Peri-Urban Areas - Jessica Frigerio; Malika Ouled Larbi; Werther Guidi Nissim; Fabrizio Grassi; Pierluigi Cortis; Massimo Labra (Diversity)
Invasive alien plants represent one of the five major threats to biodiversity and the disruption of ecosystems. They are introduced through various routes, starting with commercial trade. Preventing their introduction is essential to avoid the spread of new invasive plants. In this paper, we propose a new early warning DNA barcoding tool for invasive plant detection. Eight invasive alien species of European Union concern (i.e., Ludwigia grandiflora, Elodea nuttallii, Myriophyllum aquaticum, Pontederia crassipes, Ailanthus altissima, Heracleum mantegazzianum, Impatiens glandulifera, Pueraria montana) were selected and analysed. A unique DNA marker for each species was identified and amplified using species-specific primers capable of identifying the presence of alien species. To verify whether the approach could detect the presence of alien plants in urban areas from lawn clippings, mixes with typical urban spontaneous plants and invasive species were tested. In all mixes, only the invasive species was identified. This rapid detection capability will enable environmental operators to intervene promptly to contain the spread of invasive plants before they can cause significant damage to the local ecosystem. This tool could have a significant impact on the protection of local biodiversity and the integrity of urban habitats.